Strategies of Negative Politeness and Linguistic Realization in Thesis Advising Negotiations Via WhatsApp: A Sociopragmatic Analysis toward Quality Education (SDG 4) - Muhammad Yusi Kamhar; Kisyani Laksono; Mulyono Mulyono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To develop a conceptual framework that integrates negative politeness strategies (Brown & Levinson, 1987) with their linguistic realization (House & Kasper, 1981) in the context of thesis supervision negotiations via WhatsApp. It further examines how power, social distance, and the degree of imposition shape the selection of politeness strategies and their linguistic markers across episodes of digital academic negotiation. Method: Employing a qualitative approach, this study adopts a sociopragmatic corpus-based design using a small specialized corpus comprising 37 speech events extracted from WhatsApp interactions between undergraduate students and their thesis supervisors. The data were analyzed through a multi-layered analytical framework linking sociopragmatic variables, negative politeness strategies, and their corresponding linguistic mitigation devices. Results: Students consistently constructed request sequences using a multi-stage discourse structure consisting of greetings, apologies, the core request, and expressions of gratitude. Their requests were predominantly realized through indirect strategies (87.9%), accompanied by politeness markers such as respectful emojis (89.2%) and expressions of gratitude (86.5%). In contrast, supervisors typically responded briefly and asymmetrically, with only 29.7% of responses explicitly granting the request, reflecting an asymmetric distribution of politeness marking associated with institutional power relations. Novelty: To contribute by integrating negative politeness strategies and their linguistic realizations into a unified multi-layered analytical framework, rather than treating them as separate objects of investigation as in previous studies. It also extends the taxonomy of politeness markers by incorporating multimodal digital resources, particularly emojis, as integral components of negative politeness strategies in digital academic communication. By clarifying how respectful and equitable communication is co-constructed between students and supervisors, this study also contributes to efforts toward Quality Education (SDG 4), particularly in strengthening inclusive and supportive pedagogical relationships in higher education.